2016
DOI: 10.4103/2348-0548.190070
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of intravenous dexmedetomidine and lignocaine spray instilled into the endotracheal tube on extubation response in patients undergoing spine surgery

Abstract: Background: In spine surgery rapid emergence and extubation with haemodynamic stability is crucial for early neurological examination. Here, we have studied the effect of α2 agonist – dexmedetomidine intravenous (IV) and lignocaine spray instilled into the endotracheal tube at the end of the procedure to attenuate the extubation responses. Methods: A total of 45 patients undergoing spine surgery were randomly allocated in three groups. After the return of spontaneous respiration, Group-D: Dexmedetomidine 0.3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Dexmedetomidine induced reduction of heart rate and blood pressure is mainly dose dependent. Dutta D. et al 15 observed no incidence of bradycardia and hypotension in their study with the use of dexmedetomidine 0.3 mcg/kg. In their study they have premedicated all the patients with Glycopyrrolate 0.2mg.…”
Section: Discussionmentioning
confidence: 81%
“…Dexmedetomidine induced reduction of heart rate and blood pressure is mainly dose dependent. Dutta D. et al 15 observed no incidence of bradycardia and hypotension in their study with the use of dexmedetomidine 0.3 mcg/kg. In their study they have premedicated all the patients with Glycopyrrolate 0.2mg.…”
Section: Discussionmentioning
confidence: 81%
“…Dexmedetomidine 0.1 ug/kg resulted in a higher degree of sedation as compared to verapamil 0.3 ug/kg [5], but patients who received verapamil were anxious, agitated, and restless. The results were equivocal in studies that compared dexmedetomidine with lidocaine [24,26]. Dexmedetomidine in a dose of 0.3 and 0.5 ug/kg as compared to lidocaine did not show a significant difference in sedation [24,26].…”
Section: Alpha Agonistsmentioning
confidence: 92%
“…The results were equivocal in studies that compared dexmedetomidine with lidocaine [24,26]. Dexmedetomidine in a dose of 0.3 and 0.5 ug/kg as compared to lidocaine did not show a significant difference in sedation [24,26]. Two studies compared dexmedetomidine with opioids [3,23].…”
Section: Alpha Agonistsmentioning
confidence: 99%
See 2 more Smart Citations